The balance of rumen degradable protein and readily available carbohydrate in sheep rations on in vitro fermentability (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Protein and carbohydrates are substances needed by ruminants, especially sheep. Providing protein and carbohydrates must pay attention to their degradation. In addition, balancing nutrients to meet the nutritional needs of rumen microbes is very important because the unbalanced availability of rumen degradable protein (RDP) and readily available carbohydrate (RAC) at one time can cause suboptimal microbial protein synthesis efficiency. Materials and Methods: Completely randomized design with a nonfactorial pattern of five treatments with three replications. Treatment includes RDP and RAC ratios, namely R1 = 2.30, R2 = 2.00, R3 = 1.70, R4 = 1.50, and R5 = 1.30. Results: The results showed that the balance of RDP and RAC in sheep ration formulation in vitro had a very significant effect (p < 0.01) on NH3 , microbial protein synthesis, total gas, total microbes, and organic matter digestibility (OMD) but had no significant effect (p > 0.05) on rumen pH and dry matter digestibility (DMD). Conclusion: The optimal balance of RDP and RAC in the formulation of sheep rations in vitro was obtained at a ratio of 2.30 with NH3 (mM) 8.47, rumen pH 5.97, microbial protein synthesis (mg/100 ml) 123, gas (ml/g of material) 145, total microbes (cells/ml) 2.012 × 106 , (log CFU cells/ ml) 6.3025, DMD 61.0%, and OMD 63.1%.J. Adv. Vet. Anim. Res., 10(4): 738–743, December 2023http://doi.org/10.5455/javar.2023.j729